Optimalisasi Pemberdayaan P2MKP Tambakan Berbasis Blue Economy Upaya Meningkatkan Kemandirian Ekonomi Masyarakat Desa Bugel Kecamatan Padarincang Kabupaten Serang: Optimization of Empowerment of P2MKP Tambakan Based on Blue Economy Efforts to Increase Economic Independence of Bugel Village Community, Padarincang District, Serang Regency - Kristiyanto, Arip; Rahmawati, Iroh; Suharto, Agus; Safitri, Helen; Fadilah, Muhamad Yudi; Andriansah, Zulfi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This Community Service Program aims to optimize the empowerment of the Tambakan Independent Marine and Fisheries Training Center (P2MKP) based on the blue economy to increase the economic independence of the Bugel Village community, Padarincang District, Serang Regency. This village has significant pond fisheries potential, but its utilization has not been maximized. The blue economy approach is focused on developing sustainable and efficient fisheries. The community service methods used include financial management skills training, counseling on blue economy practices, and the development of local resource-based businesses. The results of this community service are improving community skills in managing resources and the formation of an e-commerce-based marketing system, improving neat and documented business financial records through financial system records with the SIAPIK application, blue economy-based businesses, and the formation of independent business groups. In addition, there is a higher awareness of sustainable practices and positive impacts on the environment. Thus, the economic independence of the Bugel Village community can be realized sustainably. Increased sales turnover in September to November 2024, there was an increase in sales in October by 12%, then in November 18%. Based on the survey, it stated that there was an increase in understanding related to financial management by 67%, the average value before the activity was 52.7 while after the activity it became 88.1.